Postbiotics from Saccharomyces cerevisiae fermentation stabilize rumen solids microbiota and promote microbial network interactions and diversity of hub taxa during grain-based subacute ruminal acidosis (SARA) challenges in lactating dairy cows - Guo, Junfei; Zhang, Zhengxiao; Guan, Le Luo; Zhou, Mi; Yoon, Ilkyu; Khafipour, Ehsan; Plaizier, Jan C. (Frontiers in Microbiology, 2024)
Background: High yielding dairy cows are commonly fed high grain rations. However, this can cause subacute ruminal acidosis (SARA), a metabolic disorder in dairy cows that is usually accompanied by dysbiosis of the rumen microbiome. Postbiotics that contain functional metabolites provide a competitive niche for influential members of the rumen microbiome, and, therefore, may attenuate the adverse effects of SARA. Methods: This study used a total of 32 rumen-cannulated lactating dairy cows, which were randomly assigned into four treatments: no SCFP (Control), 14 g/d Original XPC (SCFPa), 19 g/d NutriTek (SCFPb-1X), and 38 g/d NutriTek (SCFPb-2X), Diamond V, Cedar Rapids, IA) from 4 wk before until 12 wk after parturition. Grain-based SARA challenges were conducted during wk 5 (SARA1) and wk 8 (SARA2) after parturition by replacing 20% DM of the base total mixed ration (TMR) with pellets containing 50% ground barley and 50% ground wheat. The DNA of rumen solid digesta was extracted and subjected to V3-V4 16S rRNA gene sequencing. The characteristics of rumen solid microbiota were compared between non-SARA (Pre-SARA1, wk 4; Post-SARA1, wk 7; and Post-SARA2, wk 10 and 12) and SARA stages (SARA1/1, SARA1/2, SARA2/1, SARA2/2), as well as among treatments. Results: Both SARA challenges reduced the richness and diversity of the microbiota, and the relative abundances of the phylum Fibrobacteres. Supplementation with SCFP promoted the growth of several fibrolytic bacteria including Lachnospiraceae UCG-009, Treponema, unclassidied Lachnospiraceae, unclassidied Ruminococcaceae during the SARA challenges. These challenges also reduced the positive interactions and the numbers of hub taxa the microbiota. The SCFPb treatment increased positive interactions among microbial members of the digesta, as well as the numbers of hub taxa during both SARA and non-SARA stages. The SCFPb-2X treatment prevented changes in the network characteristics including the number of components, clustering coefficient, modularity, positive edge percentage and edge density of the microbiota during SARA challenges. These challenges reduced predicted carbohydrates metabolism and nitrogen metabolism in microbiota, whereas SCFP supplementation attenuated this reduction. Conclusions: Supplementation with SCFP, and especially the SCFPb-2X treatment, attenuated adverse effects of grain-based SARA on the diversity and predicted functionality of rumen solids microbiota.